Ensuring the Stability of Nonlinear Elastic and Elastoplastic Systems - Kosimovich, Kosimov Turaboy; Saidmaksudovich, Razzokov Numonkhon; Fazliddinovich, Suyunov Nodir (European Journal of Life Safety and Stability (2660-9630), 2022)
The article is devoted to determining the critical load, the solution is similar to how the problem of the stability of the cross-sectional rods was solved, the moment of inertia of which Mpr changes according to the law Jpr \u003d JE / / E. Since E / depends on the stress, which is determined by the value of the critical force, the solution of the problem will be carried out by way of posterior drink-(α)